Pancreatic Cancer Complicated by Pancreatitis Demonstrated on FDG PET/CT. (March 2017) - Hennessy, Grace; Vamadevan, Shankar; Loh, Han; Bui, Chuong; Le, Ken; Mansberg, Robert
Abstract : Abstract: A 73-year-old man was referred for 18 F-FDG PET/CT study for staging of biopsy-proven pancreatic adenocarcinoma. The scan demonstrated focal intense FDG uptake in the pancreatic head, localizing the primary tumor. Additional moderate diffuse uptake was seen throughout the pancreas, suggestive of acute pancreatitis. Concurrent diagnostic CT showed diffuse pancreatic hypoenhancement consistent with edema. Serum lipase level was elevated, confirming a diagnosis of acute pancreatitis.